Blastic Plasmacytoid Dendritic Cell Leukemia Successfully Treated by Autologous Hematopoietic Stem Cell Transplantation to a Remission of 48-Month Duration. (11th December 2013) - Goren Sahin, Deniz; Akay, Olga Meltem; Üsküdar Teke, Hava; Andıc, Neslihan; Gunduz, Eren; Gulbas, Zafer
Abstract : Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a very rare subtype of AML characterized by the clonal proliferation of precursors of plasmacytoid dendritic cells. It presents with an aggressive behavior. The clinical findings include cytopenia, particularly thrombocytopenia. Although it responds well to chemotherapy initially, the relapse is a rule and prognosis is very poor. There is limited data published in the literature, making it very problematic to define the biological and clinical features, hence, the appropriate therapeutic approach. There are various treatment methods such as multiagent chemotherapy based on ALL or AML and/or hematopoietic stem cell transplantation. However, none of them is approved as a standard therapy. From this point of view, we herein report a 20-year-old case at onset of a leukemic form of BPDCN who survived 48 months after autologous hematopoietic stem cell transplantation.